M694V gene polymorphism may not contribute to the pathogenesis of reactive arthritis in the North Indian population - Anamika Kumari Anuja; Koshy Nitin Thomas; Mantabya Kumar Singh; Ashish Jacob Mathew; Vikas Agarwal; Latika Gupta (Indian Journal of Rheumatology)
Introduction: Reactive arthritis (ReA) is a postinfectious, nonseptic arthritis that is characterized by an acute lower limb predominant oligoarthritis. Inflammasome activation and its contribution to autoinflammatory loop are described in spondyloarthritis (SpA). ReA may present a forme fruste of diseases with autoinflammation as in familial Mediterranean fever. Therefore, we investigated the presence of gene polymorphisms of the Mediterranean fever (MEFV) gene in patients with ReA. Methods: Patients of ReA presenting to a Tertiary Hospital in North India were enrolled and evaluated for MEFV gene polymorphism by restriction fragment length polymorphism analysis. Results: Forty-nine patients (male:female – 37:12), including five juvenile ReA were included during the study. The median age was 25 (±11) years and disease duration was 0.76 (±1.33) months. Twenty-six cases were triggered by preceding enteritis and 23 by urethritis. Ten healthy controls of age 27 (male:female – 7:3, interquartile range ± 1.5) were included for comparison. All 49 patients of adult and juvenile ReA were negative for the M694V mutation. Conclusions: This is the first study assessing the prevalence of MEFV gene mutation in SpA in India. It is difficult to ascertain if the lack of association is limited to the Indian subcontinent.